Geotechnical Frontiers 2017 2017
DOI: 10.1061/9780784480472.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of End-Restraint Conditions on Energy Pile Behavior

Abstract: Energy piles are deep foundation elements designed to utilize the relatively constant temperature of the ground for efficient heating and cooling of the buildings while at the same time serve as foundations. The temperature changes during the operation of energy piles result in axial displacements, a part of which is restrained by the surrounding soil or the building on top. The restrained part of the axial displacements induces compressive stresses during temperature increase and tensile stresses during tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…An alternative approach is to quantify the stiffness associated with the modeled restraint and use closed-form expressions available for such purpose [e.g., 123], which can still yield theoretical predictions representative of reality [e.g., 124,75]. Endrestraint conditions markedly characterize the significance of thermally induced stresses, strains and displacements in energy geostructures [125]. Variations in end-restraint conditions notably cause changes in the location of the null point (also called neutral plane) [97], i.e., the setting along with energy piles, barrettes and walls where zero thermally induced vertical displacements occur.…”
Section: Modeling Of Structural Restraintsmentioning
confidence: 99%
“…An alternative approach is to quantify the stiffness associated with the modeled restraint and use closed-form expressions available for such purpose [e.g., 123], which can still yield theoretical predictions representative of reality [e.g., 124,75]. Endrestraint conditions markedly characterize the significance of thermally induced stresses, strains and displacements in energy geostructures [125]. Variations in end-restraint conditions notably cause changes in the location of the null point (also called neutral plane) [97], i.e., the setting along with energy piles, barrettes and walls where zero thermally induced vertical displacements occur.…”
Section: Modeling Of Structural Restraintsmentioning
confidence: 99%
“…In addition to the previous theoretical framework addressing the response of energy piles to mechanical and thermal loads, a substantial amount of experimental knowledge can be considered to comprehensively characterize such foundations as well as to develop analysis and design considerations. Knowledge from full-scale in situ tests (Laloui et al, 2003;Bourne-Webb et al, 2009;McCartney and Murphy, 2012;Wang et al, 2014;Akrouch et al, 2014;Sutman et al, 2015;You et al, 2016;Sutman et al, 2017;Luo et al, 2017;Chen et al, 2017;Allani et al, 2017); McCartney and Murphy (2017), model-scale laboratory tests (Kalantidou et al, 2012;Yavari et al, 2014;Kramer and Basu, 2014;Marto et al, 2015;Yavari et al, 2016b;Nguyen et al, 2017;Liu et al, 2018) and centrifuge tests (Stewart and McCartney, 2014;Ng et al, 2014;Goode and McCartney, 2015;Ng et al, 2015;Ng et al, 2016a) of single energy piles is available. Along with the previous experimental knowledge, theoretical developments including numerical investigations (Laloui et al, 2006;Suryatriyastuti et al, 2012;Olgun et al, 2014;Mimouni and Laloui, 2014;Batini et al, 2015;Rotta Loria et al, 2015;Saggu and Chakraborty, 2015;Bourne-Webb et al, 2016;Gawecka et al, 2016;Ng et al, 2016b;Adinolfi et al, 2018;…”
Section: Response Of Single and Groups Of Energy Piles Subjected To T...mentioning
confidence: 99%
“…Recent studies on instrumented field-scale energy piles have mostly assessed their axial thermal responses (Laloui et al 2006;Brandl 2006;Bourne-Webb et al 2009;Murphy 2012, 2017;Akrouch et al 2014;Mimouni 2014;Mimouni and Laloui 2015;Wang et al 2015;Sutman et al 2017;Faizal et al 2016b;You et al 2016). However, only a few of these studies have been conducted under actual building loads with their outcomes reported in the literature (Brandl 2006;Laloui et al 2006;Mimouni 2014;Mimouni and Laloui 2015;Laloui 2017, 2018;Murphy 2012, 2017;Caulk et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These studies, however, need validation at various depths of a field-scale energy pile under building loads. Moreover, the thermally induced axial stresses in field-scale energy piles has been shown to significantly modify the axial mechanical loads in the pile imposed by the overlying structure (Laloui et al 2006;Bourne-Webb et al 2009;You et al 2016;Sutman et al 2017;McCartney and Murphy 2017), but the effects of radial thermal stresses on the radial mechanical loads still needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%